Clarifying the Relationship between Average Excesses and Average Effects of Allele Substitutions - Álvarez-Castro, Jose M; Yang, Rong-Cai (Frontiers in Genetics, 2012)
Fisher’s concepts of average effects and average excesses are at the core of the quantitative genetics theory. Their meaning and relationship have regularly been discussed and clarified. Here we develop a generalized set of one-locus two-allele orthogonal contrasts for average excesses and average effects, based on the concept of the effective gene content of alleles. Our developments help understand the average excesses of alleles for the biallelic case. We dissect how average excesses relate to the average effects and to the decomposition of the genetic variance.